POLA KOMUNIKASI ORANG TUA TUNGGAL DALAM KONSEP DIRI REMAJA AKHIR - Putri Apsarini, Elsa; Rina, Nofha (Medium: Jurnal Ilmiah Fakultas Ilmu Komunikasi, 2022)
Self-concept is the main factor in a person's personality that has a role in guiding and directing the development of personality and behavior in his environment. Based on a survey conducted by the Central Statistics Agency of West Java, the dominant index is anxiety and worry at 62.5%. The high level of anxiety in West Java occurs in late adolescence who transitions to young adulthood or at the college level which is generally experienced by college students. There is a study that says that self-concept is not innate, but an experience that occurs when children interact with others through connected communication. The role of the family is the main supporter in gaining experience in the form of responses so that it can provide knowledge and self-assessment to children who will later develop adolescent self-concepts. This study aims to determine how the communication patterns of single parent families in late adolescent self-concept. In this study using a qualitative method with a case study approach. Then this study uses interviews and data collection methods, the results of this study are the communication pattern carried out by single parents in adolescent self-concept is a consensual family pattern where single parents have openness and high uniformity of values in communicating within the family.